Epigenetic Biomarkers as Predictors and Correlates of Symptom Improvement Following Psychotherapy in Combat Veterans with PTSD - Yehuda, Rachel; Daskalakis, Nikolaos P.; Desarnaud, Frank; Makotkine, Iouri; Lehrner, Amy; Koch, Erin; Flory, Janine D.; Buxbaum, Joseph D.; Meaney, Michael J.; Bierer, Linda M. (Frontiers in Psychiatry, 2013)
Epigenetic alterations offer promise as prognostic or diagnostic markers, but it is not known whether these measures associate with, or predict, clinical state. These questions were addressed in a pilot study with combat veterans with PTSD to determine whether cytosine methylation in promoter regions of the glucocorticoid related NR3C1 and FKBP51 genes would predict or associate with treatment outcome. Veterans with PTSD received prolonged exposure (PE) psychotherapy, yielding responders (n=8), defined by no longer meeting diagnostic criteria for PTSD, and non-responders (n=8). Blood samples were obtained at pre-treatment, after 12 weeks of psychotherapy (post-treatment), and after a 3 month follow-up. Methylation was examined in DNA extracted from lymphocytes. Measures reflecting glucocorticoid receptor (GR) activity were also obtained from lymphocytes (i.e., plasma and 24h-urinary cortisol, plasma ACTH, lysozyme IC50-DEX, and plasma neuropetide-Y). Methylation of the GR gene (NR3C1) exon 1F promoter assessed at pre-treatment predicted treatment outcome, but was not significantly altered in responders or non-responders at post-treatment or follow-up. In contrast, methylation of the FKBP5 gene (FKBP51) exon 1 promoter region did not predict treatment response, but decreased in association with recovery. In a subset, a corresponding group difference in FKBP5 gene expression was observed, with responders showing higher gene expression at post-treatment than non-responders. Endocrine markers also changed in association with symptom change. These preliminary observations require replication and validation. However, the results support research indicating that some glucocorticoid related genes are subject to environmental regulation throughout life. Moreover, psychotherapy constitutes a form of ‘environmental regulation’ that may alter epigenetic state. Finally, the results further suggest that different genes may be associated with prognosis and symptom state, respec